Cadmium telluride nanocrystals : synthesis, growth mode and effect of reaction temperature on crystal structures - Boey, Freddy Yin Chiang (2013)
A series of cadmium telluride (CdTe) nanocrystals were synthesized by a modified organometallic synthesis method at various reaction temperatures ranging from 130 to 250°C. In this method, octadecylamine (ODA) was introduced as an additional coordinating component to the mixture of trioctylphosphine oxide (TOPO) and trioctylphosphine (TOP). CdO was used as a precursor. The prepared CdTe nanocrystals were studied by the absorption and emission spectra as well as the powder X-ray diffraction (XRD) patterns. The result shows that besides the traditional continuous-growth mode observed frequently at relatively high reaction temperature, a discontinuous-growth mode was confirmed at the initial growth stage of CdTe nanocrystals, arising from the change of the absorption spectra of CdTe nanocrystals with the reaction time at relatively low reaction temperature. The structures of CdTe nanocrystals, e.g., the cubic zinc blende structure at 160°C and the hexagonal wurtzite structure at 250°C, were characterized by XRD.